(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the theoretical and methodological foundations for developing the cognitive competence of future music teachers through interdisciplinary collaboration. It examines the modernization and effectiveness of methods aimed at enhancing cognitive competence in this context. Additionally, the article analyzes key issues in fostering cognitive competence of future music teachers based on interdisciplinary approaches.